2021
DOI: 10.5222/mmj.2021.08364
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Disorder Associated with the COVID-19 Pandemic Causes Deterioration of Blood Pressure Control in Primary Hypertensive Patients

Abstract: Objective: The new coronavirus disease (COVID-19) has spread rapidly all over the world and caused anxiety disorders. Recent studies have also shown that the prevalence of depression and anxiety increased during the COVID-19 outbreak. We aimed to evaluate the anxiety and depression levels during the pandemic and identify the effect of pandemic-related stress on blood pressure (BP) control in primary hypertensive patients. Method: A total of 142 patients with primary hypertension (HT) who continued to use the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Pengo et al showed that home BP decreased after two weeks of a COVID-19 lockdown ( 16 ). In contrast, Celik et al found that daytime, nighttime and 24-hour BP levels all increased during the COVID-19 pandemic and that anxiety intensity was associated with increased BP ( 17 ). Although there have been no reports on the effect of the COVID-19 pandemic on BP control in DM patients, the results of the present study are consistent with those of the above two studies, as the BP increased in the delayed phase rather than the acute phase.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Pengo et al showed that home BP decreased after two weeks of a COVID-19 lockdown ( 16 ). In contrast, Celik et al found that daytime, nighttime and 24-hour BP levels all increased during the COVID-19 pandemic and that anxiety intensity was associated with increased BP ( 17 ). Although there have been no reports on the effect of the COVID-19 pandemic on BP control in DM patients, the results of the present study are consistent with those of the above two studies, as the BP increased in the delayed phase rather than the acute phase.…”
Section: Discussionmentioning
confidence: 98%
“…6 ). The factors that cause different responses to worsening glycemic control and BP control are unclear, but a variety of chronic factors, including the influence of mental stress, may be involved ( 14 , 15 , 17 , 30 ). It is known that mental stress also affects blood glucose levels, but changes in the diet, activity, and medical treatment may have a greater impact on glycemic control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be because the people with formal education relied more on COVID-19 information that they collected from various sources, including the internet, which might have resulted in increased fear and anxiety. Evidence suggests that increased fear and anxiety are connected to high blood pressure [ 54 , 55 ]. A recent systematic review of 18 studies conducted in Southeast Asia reported mixed associations between education and chronic diseases related to multimorbidity [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Laffin et al, reported a rise in blood pressure in the adult population during the COVID-19 pandemic [ 19 ]. Another study conducted with adults showed that their 24 h systolic/diastolic blood pressure was significantly higher during the COVID-19 pandemic than in the pre-pandemic stage [ 20 ]. Other studies have revealed sharp high-density lipoprotein cholesterol (HDL-c) decreases [ 21 ] as well as increases in triglycerides [ 22 ], thus exacerbating the prevalence of MetS [ 23 ].…”
Section: Introductionmentioning
confidence: 99%